Facies architecture and sediment infilling processes in intrabasinal slope belts of lacustrine rift basins, Zhanhua Depression, Bohai Bay Basin. (February 2020) - Liu, Lei; Chen, Hongde; Wen, Huaguo; Xu, Wenli; Zhong, Yijiang; Wang, Xinglong; Wang, Zhiwei
Abstract: Intrabasinal slope belts, which were previously thought to lack sandy sediments, have been largely understudied due to their distance from their sediment provenance. Thus, our study sought to conduct a comprehensive geological study of the facies architecture and sediment infilling processes in the intrabasinal slope belts of the Zhanhua Depression during the Paleogene using seismic data, drill cores and well logs. Three distinctive depositional systems were identified: near-shore subaqueous fan, shallow/deep lakes, and braided-river delta. The facies architecture and sediment infilling processes were primarily characterized by different stages of diversiform tectonic geomorphologies in cyclothem motifs of rift lacustrine basins. The geomorphological characteristics of the Shahejie Formation exhibited multiple alternating uplifts and sags, resulting in multiple intra- and extra-basinal sediment provenances, while those of the Dongying Formation displayed a single depocenter with a wide and gentle geomorphology derived from several extra-basinal sediment provenances. Coarse-grained sediments formed near-shore subaqueous fans, primarily accumulated on the slopes around the Kenli Uplift during the member 3 of the Shehejie Formation interval; medium- and fine-grained sediments deposited in the proximal and distal environment of the delta front and sandy sediments formed thick-bedded sandy beach bars on subaqueous uplifts during member 2 of the Shehejie Formation interval; ultrafine-grained, fine-grained, and carbonate sediments deposited as thin-bedded carbonate banks and sandy beach bars in a shallow/deep lake during member 1 of the Shehejie Formation interval; and fine-to medium-grained sediments abundantly accumulated in the proximal environment of the delta front by passing the uplifts and infilling the slopes during the Dongying Formation interval. This integrated study demonstrates the effectiveness of a process-based analytical approach and depositional models in predicting facies architecture and sediment infilling processes. Furthermore, it provides guidelines for oil and gas exploration in intrabasinal slope belts of rift basins. Graphical abstract: Image 1 Highlights: 3D seismic data, core data, and well-logs were analysed to identify depositional systems. Strata thickness and geomorphology was restored from 3D seismic data. Facies architecture and sediment infill process of intra-basinal slopes are studied.